Influence of molecular weight on the non-isothermal melt crystallization of biodegradable poly(D-Lactide) - Wanich Limwanich (2018)
© 2017 Trans Tech Publications, Switzerland. The influence of molecular weight of poly(D-lactide) (PDL) on the melt crystallization was successfully investigated by non-isothermal differential scanning calorimetry (DSC) technique. The synthesized PDLs with three different number average molecular weights ( n M ) of 2.39×105 (PDL1), 1.09×105 (PDL2) and 0.61×105 (PDL3) were utilized in this study. From DSC kinetics analysis, it was found that the rate of PDLs crystallization increased with increasing cooling rate. Furthermore, the crystallization rate of PDLs was dependent on molecular weight and determined to be in the following order: PDL3 > PDL2 > PDL1. The crystallization mechanism was analyzed by the Avrami, Ozawa and Liu models. The mechanism of all PDLs crystallization was nucleation with three dimensional growths. Furthermore, the molecular weight of PDLs affected not only the crystallization rate but also the thermal property. As the molecular weight of PDLs increased, the melting temperature (Tm) increased but the heat of melting (ΔHm) decreased.